Mouse Cytomegalovirus M34 Encodes a Non-essential, Nuclear, Early-Late Expressed Protein Required for Efficient Viral Replication - Eilbrecht, Mareike; Le-Trilling, Vu Thuy Khanh; Trilling, Mirko (Frontiers in Cellular and Infection Microbiology, 2020)
Human cytomegalovirus (HCMV) is a prototypic betaherpesvirus which causes severe manifestations in individuals with impaired or immature immunity. To investigate cytomegalovirus-induced pathogenesis and virus-specific immune responses, mouse cytomegalovirus (MCMV) infections in mice are employed as accepted small animal model. MCMV and HCMV share co-linear genomes and encode several homologous proteins. Due to the size and complexity of CMV genomes, the molecular functions of numerous cytomegaloviral gene products remain to be elucidated. While the essential nature of viral genes highlights their biological relevance, it renders functional studies particularly cumbersome by precluding experiments in the infection context. The HCMV-encoded protein pUL34 binds the HCMV genome and regulates viral gene expression (e.g., of US3). Several groups provided compelling evidence that UL34 is essential for HCMV replication. MCMV encodes the homologous protein pM34 (34% identical and 55% similar). Based on unsuccessful attempts to reconstitute M34-deficient virus from a bacterial artificial chromosome (BAC), M34 was previously classified as essential for MCMV replication. To characterize pM34 during viral infection, we engineered and analyzed an MCMV mutant expressing an HA-epitope-tagged pM34 which was expressed with early-late kinetics and localized in the nucleus. Additionally, we generated an M34-deficient (“ΔM34”) MCMV-BAC by replacing the entire M34 coding sequence by a kanamycin resistance cassette. The deletion of M34 was confirmed by Southern blot and PCR. Unexpectedly, we could reconstitute replicating ΔM34-MCMV upon transfection of the BAC DNA into mouse embryonic fibroblasts. The absence of M34 from the genome of the replicating ΔM34-MCMV was also confirmed. Accordingly, a ΔM34-MCMV, in which the kanamycin cassette was excised by frt/Flp-mediated recombination, was also replication competent. In order to corroborate the absence of pM34 protein, the M34 deletion was recapitulated on the background of M34HA, which yielded replicating virus devoid of detectable pM34HA protein. The replication of MCMVs lacking M34 was found to be 10- to 100-fold reduced as compared to wt-MCMV which might explain previous unsuccessful reconstitution attempts conducted by others. Taken together, our findings reveal that MCMV remains replication competent despite the absence of M34, enabling functional studies in the infection context.